2000
DOI: 10.1097/00005392-200007000-00065
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavengers, Catalase and Superoxide Dismutase Provide Protection From Oxalate-Associated Injury to LLC-Pk1 and MDCK Cells

Abstract: Results of the present study indicate that both Ox and COM crystals are injurious to renal epithelial cells and the injury is associated with generation of free radicals. Cells of proximal tubular origin are more susceptible than those of distal tubules and collecting ducts. Free radical scavengers, catalase and SOD provide significant protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 29 publications
5
66
0
Order By: Relevance
“…Our previous studies [19], as well as those of others [24], demonstrated that oxalate exposure increases free radical production in renal epithelial cells. When we expose cells to oxalate concurrent with calcium oxalate monohydrate (COM) crystals, the production of ROS is greater than in cells exposed to oxalate alone [19]. Similarly, oxalate exposure results in increased MDA content and this effect is further enhanced by the addition of COM crystals to renal tubular cells [19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous studies [19], as well as those of others [24], demonstrated that oxalate exposure increases free radical production in renal epithelial cells. When we expose cells to oxalate concurrent with calcium oxalate monohydrate (COM) crystals, the production of ROS is greater than in cells exposed to oxalate alone [19]. Similarly, oxalate exposure results in increased MDA content and this effect is further enhanced by the addition of COM crystals to renal tubular cells [19].…”
Section: Discussionmentioning
confidence: 88%
“…Lipid peroxidation was measured as MDA content, a product of lipid peroxidation, using a thiobarbituric acid method as previously described [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Further experiments on MDCK and LLC-PK1 (pig kidney epithelial cells with properties of proximal tubule epithelial cells) monolayers showed that crystal-related cell damage is associated with an increased production of free radicals and cell death. These phenomena were related to oxalate concentration, whereas free radical scavenging and degrading enzymes such as catalase (CAT) and superoxide dismutase (SOD) provided strong protection from the injury (52,53). In experiments with fresh rat urothelium, crystals formed at the site of the damaged superfi cial cells in a free radical-rich environment, whereas administration of antioxidants (mannitol or ascorbic acid) abolished crystal formation (54).…”
Section: Formation Of Oxalate Crystals and Onset Of Ksdmentioning
confidence: 99%
“…SOD catalyzes the conversion of superoxides (O2 · ) into H2O2; the H2O2 is further reduced to H2O by CAT. Treatment with CAT and SOD helps prevent ROS-induced damage in LLC-PK1 cells [36,44] and reduced the oxidative stress-induced lipid peroxidation in vivo [45]. GSH-px catalyzed the intercellular reduced GSH which as a hydrogen donor to generate oxidized glutahthine(GSSG), and eliminated H2O2 and catalyzed the reduction of peroxides in living organ [46,47].…”
Section: Discussionmentioning
confidence: 99%